Ilokusi Komisif dalam Iklan Traveloka di Youtube dan Implikasinya terhadap Pembelajaran Bahasa Indonesia di SMP: Studi Pragmatik - Astuti, Tria Puji; Rusminto, Nurlaksana Eko; Prasetyo, Heru (Edukasi Lingua Sastra, 2025)
The aim of this study is to describe the communicative function of commissive illocutionary acts in Traveloka advertisements on YouTube based on the continuity and literality of the utterances. The research method used is descriptive qualitative. The data source in this study consists of Traveloka advertisements on YouTube. The research data comprises commissive illocutionary utterances delivered by speakers in the Traveloka advertisements on YouTube. Data collection was carried out using non-test techniques, namely non-participatory observation and documentation, to gather commissive illocutionary acts found in Traveloka advertisements on YouTube. The researcher observed the advertisements available on YouTube without being directly involved in the speech events. The data were recorded using descriptive and reflective field notes. The data analysis technique used was heuristic analysis. The results of the study show that there are commissive illocutionary acts in Traveloka advertisements on the Traveloka Indonesia YouTube channel, which include the communicative functions of promising, offering, and pledging. Based on the continuity and literality of the utterances, the commissive illocutionary acts are expressed in forms that are direct and literal, indirect and literal, as well as indirect and non-literal. The findings of this study are utilized in the development of teaching materials.